2020
DOI: 10.1002/jez.b.22930
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic canalization and its limits—A view from temperature

Abstract: Many animals are able to produce similar offspring over a range of environmental conditions. This property of the developmental process has been termed canalization—the channeling of developmental pathways to generate a stable outcome despite varying conditions. Temperature is one environmental parameter that has fundamental effects on cell physiology and biochemistry, yet developmental programs generally result in a stable phenotype under a range of temperatures. On the other hand, there are typically upper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 145 publications
(199 reference statements)
0
16
0
Order By: Relevance
“…The offspring used in this study were sampled at the fry (i.e. early exogenous feeding) stage, thus it is possible that brook charr may exhibit greater plasticity later in development, due to either strong parental effects during early life stages, or developmental canalization resulting in low plasticity during early life [ 88 ]. Other studies have identified long-lasting parental effects on gene expression [ 18 ] and offspring size [ 89 , 90 ] in brook charr, and a related study using Laval strain brook charr identified persistent parental effects on phenotype past stocking [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The offspring used in this study were sampled at the fry (i.e. early exogenous feeding) stage, thus it is possible that brook charr may exhibit greater plasticity later in development, due to either strong parental effects during early life stages, or developmental canalization resulting in low plasticity during early life [ 88 ]. Other studies have identified long-lasting parental effects on gene expression [ 18 ] and offspring size [ 89 , 90 ] in brook charr, and a related study using Laval strain brook charr identified persistent parental effects on phenotype past stocking [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nor does it imply that the temperature T fully defines the window duration. Studies indicate that temperature stress weeks before hatching, in the gastrulation phase (Irvine, 2020; Mueller et al, 2015) could alter the efficiency of respiration and cellular development, which in turn could affect the coefficients in Equation ().…”
Section: Methodsmentioning
confidence: 99%
“…If inherited differences in DNA methylation affect offspring phenotype, epigenetic inheritance due to parental thermal regime could prove adaptive for brook charr due to gradual but predictable warming in Canada, but maladaptive if brook charr are unable to acclimate to and survive transient temperature extremes. The offspring used in this study were sampled at the fry (i.e., early exogenous feeding) stage, thus it is possible that brook charr may exhibit greater plasticity later in development, due to either strong parental effects during early life stages, or developmental canalization resulting in low plasticity during early life [83]. Other studies have identified long-lasting parental effects on gene expression [18] and offspring size [84,85] in brook charr, and a related study using Laval strain brook charr identified persistent parental effects on phenotype past stocking [54].…”
Section: Discussionmentioning
confidence: 99%